Soucasné moznosti lécby sarkoidózy - Slováková, A; Votava, V; Homolka, J (Casopis lekaru ceskych, 2007)
When to start the treatment of sarcoidosis and what are the optimal treatment methods? The curative of the first choice are glucocorticoids used in indicated cases in general administration, as inhalation therapy or locally in the skin manifestations. Frequently used are also immunosuppressives, cytostatics and antimalarics. The newest trend in the treatment of this multi-organ granulomatose disease of unknown origin is the use of TNF inhibitors--pentoxifyllin, infliximab, adalimumab, leflunomid, thalidomid.
Keywords: Tumor Necrosis Factor-alpha; Humans; Sarcoidosis; sarkoidóza; lidé; TNF-alfa